THE NEWSLETTER ON THE RUSSIAN CONGRESS OF CARDIOLOGY “EFFICACY AND SAFETY OF DIAGNOSTICS AND TREATMENT” (Российский кардиологический журнал)
The newsletter on the Russian Congress of Cardiology “Efficacy and safety of diagnostics and treatment”.